Modeling and controller design architecture for cycle-by-cycle combustion control of homogeneous charge compression ignition (HCCI) engines – A comprehensive review - Fathi, Morteza; Jahanian, Omid; Shahbakhti, Mahdi (Energy conversion and management, 2017)
•Addressing accuracy-speed compromise of HCCI representation is very important.•Phasing, load, exhaust temperature and emissions are the most important outputs.•Separability between the effects of the inputs on the outputs is of great interest.•Existing actuation systems combining inputs are favorable.•An HCCI controller should be a fast and robust one to become a viable solution. Homogeneous charge compression ignition (HCCI) combustion engines are advantageous in terms of good fuel economy and low levels of soot-nitrogen oxides (NOx) emissions. However, they are accompanied with some intrinsic challenges, the most important of which is the lack of any direct control method for ignition trigger. Thus, implementation of HCCI combustion is in fact a control problem, and an optimized control structure is required for attaining the inherent benefits of HCCI. The control structure consists of a proper representation of engine processes; a suitable selection of state variables; useful and applicable set of inputs, outputs and observers; appropriate fixed or variable set-points for controlled parameters; instrumentations including sensors and actuators; and an applicable control law implemented in a controller. The present paper aims at addressing these issues altogether by introducing HCCI engine control structure in progress and presenting highlights from literature. Research should result in appropriately controlled HCCI engines which can provide desired load at rated speed with acceptable performance and emissions characteristics.